Copyright Literacy of Library and Information Science Professionals in India: A Survey - Naheem, K. T. (Journal of Information and Knowledge, 2020)
This paper presents the results of an online survey of Indian Library and Information Science (LIS) professionals’ knowledge and awareness about copyright-related issues. Results of the study unveil the copyright literacy level of Indian LIS professionals. Only a small proportion of respondents are familiar with copyright related issues. It is concluded that the level of familiarity of Indian LIS professionals with issues concerning copyright is inadequate as compared to the significance of the topic.